2016
DOI: 10.1007/s12062-016-9148-0
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-being Across the Lifespan in Europe and Central Asia

Abstract: Using data from the Integrated Values Survey (IVS), the Life in Transition Survey (LiTS), and the Russia Longitudinal Monitoring Survey (RLMS), we analyse the relation between age and subjective well-being in the World Bank's Europe and Central Asia (ECA) region and compare it to that in Western Europe. Although our results generally confirm previous studies' findings of a U-shaped relation between subjective well-being and age for most of the lifecycle, we also find that well-being in ECA declines again after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
5
14
0
Order By: Relevance
“…Table 1 reveals that several cross-sectional studies documented a U shape using life satisfaction, the Cantril ladder, and happiness items (Beja, 2018; Cheng et al, 2015; Daroudi, Rashidian, Zeraati, Oliyaeemanesh, & Sari, 2016; Graham & Pozuelo, 2017; Grover & Helliwell, 2019; Lin, 2016; Ruseski, Humphreys, Hallman, Wicker, & Breuer, 2014; Schwandt, 2016), but others found mixed evidence. That is, the shape (and associated nadirs and peaks) of the age-happiness connection varied depending on the country and region of the world (Bauer, Levin, Boudet, Nie, & Sousa-Poza, 2017; Laaksonen, 2018; Morgan, Robinson, & Thompson, 2015; Steptoe et al, 2015), whether control variables such as education and marital status were included in the analyses (Blanchflower & Oswald, 2019; Ferrante, 2017; Hellevik, 2017), year or period of time when the surveys were administered (Kolosnitsyna, Khorkina, & Dorzhiev, 2017; Olaroiu, Alexa, & van den Heuvel, 2017), and gender (Kolosnitsyna et al, 2017; Laaksonen, 2018). Some studies found a U shape, but the low point was outside of the typical range of midlife (defined as 40–60 years of age; Freund & Ritter, 2009), for example, in the 30s (Laaksonen, 2018; Li, 2016) or up to age 70 (Kolosnitsyna et al, 2017).…”
Section: Cross-sectional Support For the U Shape Is Mixedmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 reveals that several cross-sectional studies documented a U shape using life satisfaction, the Cantril ladder, and happiness items (Beja, 2018; Cheng et al, 2015; Daroudi, Rashidian, Zeraati, Oliyaeemanesh, & Sari, 2016; Graham & Pozuelo, 2017; Grover & Helliwell, 2019; Lin, 2016; Ruseski, Humphreys, Hallman, Wicker, & Breuer, 2014; Schwandt, 2016), but others found mixed evidence. That is, the shape (and associated nadirs and peaks) of the age-happiness connection varied depending on the country and region of the world (Bauer, Levin, Boudet, Nie, & Sousa-Poza, 2017; Laaksonen, 2018; Morgan, Robinson, & Thompson, 2015; Steptoe et al, 2015), whether control variables such as education and marital status were included in the analyses (Blanchflower & Oswald, 2019; Ferrante, 2017; Hellevik, 2017), year or period of time when the surveys were administered (Kolosnitsyna, Khorkina, & Dorzhiev, 2017; Olaroiu, Alexa, & van den Heuvel, 2017), and gender (Kolosnitsyna et al, 2017; Laaksonen, 2018). Some studies found a U shape, but the low point was outside of the typical range of midlife (defined as 40–60 years of age; Freund & Ritter, 2009), for example, in the 30s (Laaksonen, 2018; Li, 2016) or up to age 70 (Kolosnitsyna et al, 2017).…”
Section: Cross-sectional Support For the U Shape Is Mixedmentioning
confidence: 99%
“…The Midlife in the United States (MIDUS) study followed 10-year age bands of adults ages 25 to 75 for a decade; there was no change in life satisfaction from the 20s to the 40s, but life satisfaction increased from the 40s to the 60s and was followed by a decline until the age of 70 (Lachman, Teshale, & Agrigoroaei, 2015). Data from the Russia Longitudinal Monitoring Survey, which followed multiple age cohorts from the teens to the 80s, documented several age patterns in life satisfaction (U-shaped, S-shaped, downward, and upward) depending on the analysis (Bauer et al, 2017).…”
Section: Longitudinal Support For the U Shape Is Mixedmentioning
confidence: 99%
“…Since the LITS allow for full cross-country comparability, the survey has been used in a variety of comparative health research (e.g. Bauer et al, 2017; Nikolova and Sanfey, 2016) [5354]. Here, we focus on Armenia, Azerbaijan, Belarus, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Russia, Tajikistan, Ukraine, and Uzbekistan.…”
Section: Methodsmentioning
confidence: 99%
“…In the fifth and final step, one member of each identified household was selected for interview with a trained interviewer based on the “last birthday” selection rule. Because of its full cross-country comparability and high quality, the LITS has been used in several comparative health studies [122526].…”
Section: Methodsmentioning
confidence: 99%